Calcium in the Backstage of Malaria Parasite Biology - de Oliveira, Lucas Silva; Alborghetti, Marcos Rodrigo; Carneiro, Renata Garcia; Bastos, Izabela Marques Dourado; Amino, Rogerio; Grellier, Philippe; Charneau, Sébastien (Frontiers in Cellular and Infection Microbiology, 2021)
The calcium ion (Ca2+) is a ubiquitous second messenger involved in key biological processes in prokaryotes and eukaryotes. In Plasmodium species, Ca2+ signalling plays a central role in the parasite life cycle. It has been associated with parasite development, fertilization, locomotion, and host cell infection. Despite the lack of a canonical inositol-1,4,5-triphosphate receptor gene in the Plasmodium genome, pharmacological evidence indicates that inositol-1,4,5-triphosphate triggers Ca2+ mobilization from the endoplasmic reticulum. Other structures such as acidocalcisomes, food vacuole and mitochondria are proposed to act as supplementary intracellular Ca2+ reservoirs. Several Ca2+-binding proteins (CaBPs) trigger downstream signalling. Other proteins with no EF-hand motifs, but apparently involved with CaBPs, are depicted as playing an important role in the erythrocyte invasion and egress. It is also proposed that a cross-talk among kinases, which are not members of the family of Ca2+-dependent protein kinases, such as protein kinases G, A and B, play additional roles mediated indirectly by Ca2+ regulation. This statement may be extended for proteins directly related to invasion or egress, such as SUB1, ERC, IMC1I, IMC1g, GAP45 and EBA175. In this review, we update our understanding of aspects of Ca2+-mediated signalling correlated to the developmental stages of the malaria parasite life cycle.